2020
DOI: 10.3389/fimmu.2020.568685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiota in Neutrophil Regulation and Adaptation in Newborns

Abstract: Newborns are highly susceptible to infections and mainly rely on innate immune functions. Reduced reactivity, delayed activation and subsequent failure to resolve inflammation however makes the neonatal immune system a very volatile line of defense. Perinatal microbiota, nutrition and different extra-uterine factors are critical elements that define long-term outcomes and shape the immune system during the neonatal period. Neutrophils are first responders and represent a vital component of the immune system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 142 publications
0
23
0
1
Order By: Relevance
“…Taken together, the induction of opposing immune reactions shaped by LPS may serve as a binary switch to either efficiently eradicate pathogens (training as a resistance mechanism), or to support the resolution of inflammation (tolerance as persistence response) [25,84]. Recent studies on trained neutrophils, which may alter the diseases state or promote anti-tumoral activities, highlight the importance of memory-like responses during pathologies [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the induction of opposing immune reactions shaped by LPS may serve as a binary switch to either efficiently eradicate pathogens (training as a resistance mechanism), or to support the resolution of inflammation (tolerance as persistence response) [25,84]. Recent studies on trained neutrophils, which may alter the diseases state or promote anti-tumoral activities, highlight the importance of memory-like responses during pathologies [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are among the first responder cells of the innate immunity that enter the site of infection. They are the most abundant type of immune cells and the largest group of polymorphonuclear cells [23][24][25]. As terminally differentiated cells, neutrophils harbor an armory of antimicrobial agents, such as hydrolytic enzymes and pro-inflammatory mediators, and produce reactive oxygen species (ROS) in order to protect against a variety of different viral, bacterial, as well as fungal infections [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by our group revealed that microglia from neonatal brains display features of trained immunity and immune tolerance after repeated contact with pathogens in a dose-dependent manner [ 10 , 46 ]. Intriguingly, naïve microglia exhibit a remarkable sensitivity to bacterial PAMPs [ 47 ], possibly to prevent hazardous events in newborns, who are highly susceptible to infections and mainly rely on innate immunity [ 48 ]. Our findings confirmed the high susceptibility of microglia to PAMPs by showing that priming with ultralow LPS dosages induced elevated proinflammatory responses [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study uncovers the inhibition of PI3Kγ lipid kinase activity as a mechanism causing suppression of the microglial proliferation of LPS or ATP. The dose levels of the prototypical bacterial PAMP as well as the DAMP triggering robust microglial activation used in our in vitro systems were based on our previous work [10,24,29,44]. Nevertheless, it should be recognized that relevant cellular immune responses can be induced-at least in naïve microglia-with much lower LPS concentrations.…”
Section: Discussionmentioning
confidence: 99%